2013
DOI: 10.1007/s00382-013-2002-7
|View full text |Cite
|
Sign up to set email alerts
|

Future change of the Indian Ocean basin-wide and dipole modes in the CMIP5

Abstract: The Indian Ocean sea surface temperature (SST) variability has been represented with the two dominant variability modes: the Indian Ocean basin-wide (IOBW) and dipole (IOD) modes. Here we investigate future changes of the two modes together with mean state and El Niño and Southern Oscillation (ENSO) relationship under the anthropogenic global warming using 20 coupled models that participated in the phase five of Coupled Model Intercomparison Project by comparing the historical run from 1950 to 2005 and the RCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 33 publications
3
59
0
3
Order By: Relevance
“…An early study based on a single model (Zheng et al, 2011) showed that in a warmer climate both the IO warming and AAC persist longer in post-El Niño summer, indicating a strengthening of the positive feedback from the interaction of these interannual ocean-atmosphere anomalies. A similar strengthening of the IPOC mode takes place in a subset of CMIP5 models that are deemed to simulate the mode well in current climate (Chu et al, 2014). showed that by changing the moist adiabatic lapse rate, climate warming amplifies the tropospheric Kelvin wave that connects the Indo-western Pacific oceans in post-El Niño summer.…”
Section: Discussionmentioning
confidence: 96%
“…An early study based on a single model (Zheng et al, 2011) showed that in a warmer climate both the IO warming and AAC persist longer in post-El Niño summer, indicating a strengthening of the positive feedback from the interaction of these interannual ocean-atmosphere anomalies. A similar strengthening of the IPOC mode takes place in a subset of CMIP5 models that are deemed to simulate the mode well in current climate (Chu et al, 2014). showed that by changing the moist adiabatic lapse rate, climate warming amplifies the tropospheric Kelvin wave that connects the Indo-western Pacific oceans in post-El Niño summer.…”
Section: Discussionmentioning
confidence: 96%
“…A total of 20 coupled general circulation models (CGCMs) that participated in the CMIP5 were utilized in this study, following several previous studies (Chu et al 2014;Lee et al 2014;Chen et al 2016). Although more CMIP5 models could be available now, the use of the same 20 models provides a fair comparison with the previous results in the multimodel framework.…”
Section: Observation and Cmip5 Model Datamentioning
confidence: 98%
“…Taking into account the limited sample size in observational data, the Coupled Model Intercomparison Project phase 5 (CMIP5) historical simulations for the twentieth century are used. It has been reported that most CMIP5 models reasonably capture spatial distribution, seasonality, and periodicity of the IOBM and IOD modes (Du et al 2013;Chu et al 2014;Liu et al 2014) in addition to ENSO (Bellenger et al 2014;Lee et al 2014;Chen et al 2016). Furthermore, several studies (e.g.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…이 모델들은 해양, 대기 그리고 지구상 생물권에 존재하는 탄소의 양 사이에서 탄소의 중요한 플럭스 를 설명하고, 어떤 경우에는 상호적인 전조가 되는 에 어로졸과 화학적, 역학적인 식생 요소를 포함하는 생 물-지구화학 요소를 포함한다 (Taylor et al, 2012;Lee and Wang, 2014;Chu et al, 2014). 그러므로 CMIP5 문혜진·김병희·오효은·이준이·하경자 405 는 CMIP3 보다 자연적인 강제력과 에어로졸에 더 크 게 반응할 것이다 (Yeh et al, 2012).…”
Section: 자료 및 분석 방법unclassified